Analisis Pengukuran Kinerja Organisasi Pengelolaan Zakat pada Lembaga Amil Zakat (LAZ) Zakat Sukses - Ade Fitria Agustina (Neolectura, 2019)
The purpose in this research was to determine the performance of amil zakat institutions (laz) on zakat success. The measurement methods used by the prime performance measurement methods issued by IMZ in the 2011 Indonesian Zakat and Development Report (IDZR) consist of a proportion of the five components of the OPZ measurement including: (1) Sharia compliance, legality and institutional performance, (2) Management performance, ( 3) Financial performance (4) Performance of economic empowerment, and (5) Performance of social legitimacy. the results of the performance evaluation of Zakat Sukses are for assessments of shariah compliance, legality and institutional performance, achieving the highest score of getting a score (7.6) or rating B. The second best rating is in terms of management with a total value (6.6), then following successively the third best ranking. namely financial performance, economic empowerment performance and legistimacy performance with a total value (6). Overall, the value obtained is (6.46) or C. This it can be concluded that in general, the performance of Zakat Sukses is quite good. therefore a small value does not mean the performance of zakat institutions results in poor performance, but rather because of the unavailability of data for assessment on related components. for that LAZ Zakat Success to continue to strive to complete the shortcomings.